Towards a Better Understanding of the Chronological and Geographical Distribution Patterns of Plain and Painted Handmade Wares in Bilād al-Shām - Makowski, Piotr Tomasz (Bulletin of ASOR, 2023)
Though it has now been more than 90 years since the phenomenon of plain and painted handmade wares first became apparent to field archaeologists working at historical sites in the territory of Bilād al-Shām, so far relatively little effort has been made to explain it sufficiently. The current paper provides an introductory survey of the available literature and attempts to organize the overall discussion regarding the patterns of their chronological and geographical distribution. Particular attention has been paid to the dating of the appearance of handmade wares and the first phase of their development. Illustrating the occurrence of handmade wares in the form of maps and charts, this article also intends to assess the regional differences in their status as well as the mutual relationship between plain and painted wares.